Prolonging life: legal, ethical, and social dilemmas. (30th July 2014) - Paulson, Steve; Comfort, Christopher P.; Lee, Barbara Coombs; Shemie, Sam; Solomon, Mildred Z.
Abstract : The ability of modern medicine to prolong life has raised a variety of difficult legal, ethical, and social issues on which reasonable minds can differ. Among these are the morality of euthanasia in cases of deep coma or irreversible injury, as well as the Dead Donor Rule with respect to organ harvesting and transplants. As science continues to refine and develop lifesaving technologies, questions remain as to how much medical effort and financial resources should be expended to prolong the lives of patients suspended between life and death. At what point should death be considered irreversible? What criteria should be used to determine when to withhold or withdraw life‐prolonging treatments in cases of severe brain damage and terminal illness? To explore these complex dilemmas, Steve Paulson, executive producer and host of To the Best of Our Knowledge, moderated a discussion panel. Pediatrician Sam Shemie, hospice medical director Christopher P. Comfort, bioethicist Mildred Z. Solomon, and attorney Barbara Coombs Lee examined the underlying assumptions and considerations that ultimately shape individual and societal decisions surrounding these issues. The following is an edited transcript of the discussion that occurred November 12, 2013, 7:00–8:30 PM, at the New York Academy of Sciences in New York City.